Preventing a spillover of the Iran-Israel conflict in Syria: E3+Russia should lead the way out - Gil David Murciano (Stiftung Wissenschaft und Politik (SWP), 2018)
Israel's containment policy vis-à-vis Iran in Syria has entered a new phase of direct confrontation aimed at achieving a decisive outcome on the ground. Israeli decision-makers now see a window of opportunity to remove Iran's long-term military presence in Syria through a combination of military and diplomatic means. Israel's approach is based on the assessment that this goal can be achieved while containing the fighting to the Syrian arena. Nevertheless, this new strategic attitude increases the likelihood of a spillover beyond the Syrian arena and into a regional conflict. Iran's military actions in Syria have demonstrated that its goals exceed the logic of defensive deterrence and are driven by an ambition to increase its offensive potential vis-à-vis Israel. Germany should take an active role in a coordinated effort by the E3 countries (Germany, France, and the United Kingdom) and Russia to pressure Iran to scale-down its military presence while providing it with a face-saving framework to protect its core political interests.
Keywords: 320